2006
DOI: 10.1093/eurheartj/ehl095
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural evidence of intercalated disc remodelling in arrhythmogenic right ventricular cardiomyopathy: an electron microscopy investigation on endomyocardial biopsies

Abstract: The ultrastructural evidence of intercalated discs remodelling in ARVC, together with the positive screening of D protein encoding genes in half of probands, are in keeping with an intercellular junction cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
120
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(137 citation statements)
references
References 33 publications
12
120
0
5
Order By: Relevance
“…2 Recent studies highlight that desmosomal mutations may lead to a remodelling inside the area composita and a defective distribution of ion channel molecules, but not necessarily to decreased levels of other desmosomes in general. 24 In line with those studies, our analysis revealed that in patients with ARVC/D, there is no general decrease in all desmosomal mRNAs, but that pathogenic desmosomal nonsense or frameshift mutations may lead to decreased levels of those particular desmosomal molecules. 25,26 Phospholamban PLN is a protein linked to the sarcoplasmatic reticulum, inhibiting the calcium intake when dephosphorylated, and increasing myocardial contractility through calcium intake when phosphorylated.…”
Section: Desmosomal Moleculessupporting
confidence: 89%
“…2 Recent studies highlight that desmosomal mutations may lead to a remodelling inside the area composita and a defective distribution of ion channel molecules, but not necessarily to decreased levels of other desmosomes in general. 24 In line with those studies, our analysis revealed that in patients with ARVC/D, there is no general decrease in all desmosomal mRNAs, but that pathogenic desmosomal nonsense or frameshift mutations may lead to decreased levels of those particular desmosomal molecules. 25,26 Phospholamban PLN is a protein linked to the sarcoplasmatic reticulum, inhibiting the calcium intake when dephosphorylated, and increasing myocardial contractility through calcium intake when phosphorylated.…”
Section: Desmosomal Moleculessupporting
confidence: 89%
“…the armadillo proteins (junction plakoglobin and plakophilins), cadherins (desmocollins and desmogleins), and plakins (desmoplakin). Even before the discovery of desmosomal genes in AC, electron microscopy studies demonstrating intercalated disc remodelling first raised the hypothesis of an abnormal cell-cell adhesion in disease pathogenesis [89,90]. More recently, Sato et al, using monolayers of neonatal rat ventricular myocytes in which PKP2 was silenced and subjected to a defined mechanical intervention, demonstrated a reduced cell-cell adhesion [91].…”
Section: Abnormal Cell-cell Adhesionmentioning
confidence: 99%
“…Five of the causal genes are coding for desmosomal proteins (Gerull et al 2004;McKoy et al 2000;Norgett et al 2000;Sen-Chowdhry et al 2005;Syrris et al 2007). Though electron microscopy of endomyocardial biopsies of ARVC patients revealed remodelling of intercalated discs and abnormal desmosomes, the molecular pathomechanisms are largely unknown (Basso et al 2006). Paired myocardial samples from the left (LV) and right ventricles (RV) were obtained from six non-failing (NF) donor hearts, six ARVC patients and seven patients with idiopathic dilated cardiomyopathy (DCM).…”
mentioning
confidence: 99%